Convergent Visions, Divergent Practices: Managing Pesantren and National Curriculum Integration in Indonesian Islamic Boarding Schools - Muhammad Ishomudin; M. Ainur Rifqi; Ayu Wulandari (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2026)
This study aimed to examine how pesantren and national curricula are integrated across two Islamic boarding schools. Curriculum integration is challenging because institutions must reconcile national standards with religious traditions, character formation, and competencies. Different pesantren contexts may produce distinct configurations despite educational ideals. A multisite qualitative case study was conducted at Amanatul Ummah Pacet and Al-Amanah Junwangi. Data were collected through interviews, observations, and document analysis, then analyzed through condensation, display, and verification. The first finding shows that both institutions share an ulul albab-oriented vision integrating IMTAQ and IPTEK. However, Amanatul Ummah emphasizes classical scholarship and tahfidz, while Al-Amanah prioritizes bilingualism, life skills, and competency-based programs. The second finding reveals that integration operates through twenty-four-hour activities. Amanatul Ummah applies intensive time zoning, whereas Al-Amanah uses modular, technology-supported learning arrangements. Both sites face student fatigue and respond through interactive pedagogy. The third finding demonstrates multidimensional authentic evaluation combining academic, religious, character, and practical evidence. This study contributes a contextualized multisite model linking institutional vision, learning ecology, and authentic evaluation. It also offers guidance for designing coherent, identity-sensitive, student-responsive integrated curricula.